Inorganic polyphosphate–an unusual suspect of the mitochondrial permeability transition mystery - Seidlmayer, Lea K. (Landes Bioscience, 2012)
Inorganic polyphosphate (polyP) is a naturally occurring polyanion made of ten to several hundred orthophosphates (P(i)) linked together by phosphoanhydride bonds. PolyP is ubiquitously present in all organisms from bacteria to humans. Specific physiological roles of polyP vary dramatically depending on its size, concentration, tissue and subcellular localization. Recently we reported that mitochondria of ventricular myocytes contain significant amounts (280 ± 60 pmol/mg of protein) of polyP with an average length of 25 orthophosphates, and that polyP is involved in Ca(2+)-dependent activation of the mitochondrial permeability transition pore (mPTP). Here we extend our study to demonstrate the involvement of mitochondrial polyP in cardiac cell death. Furthermore, we show that polyP levels depend on the activity of the respiratory chain and are lower in myocytes from failing hearts. We conclude that polyP is a dynamically regulated macromolecule that plays an important role in mPTP-dependent cell death pathway.